A Study of Rhodamine-6G Stain Expression for Detection and Association of Copper Content in Potentially Malignant Disorders and Squamous Cell Carcinoma - Himanshu Singh1 , Sushruth Nayak2 , Prachi Nayak3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim and Objective: To assess the expression of Rhodamine-6G stain in potentially malignant disorders andSCC and to determine association of copper in potentially malignant disorders and OSCC.Materials and Method: Sections from ten tissue blocks of each normal oral mucosa, oral leukoplakia,oral sub mucous fibrosis (OSMF), well differentiated squamous cell carcinoma (WDSCC) and moderatelydifferentiated squamous cell carcinoma (MDSCC) was taken and stained with Rhodamine-6g stain. Afteradequate staining, all the samples were assessed using Fluorescence microscope for the color intensity anddepth of penetration of copper and compared.Results: It showed significant Pearson chi square values of 0.157 for color intensity of copper and 0.019for depth of penetration of copper. Pearson correlation was calculated which showed significant value forleukoplakia (0.055)* in comparison to OSMF (0.429), WDSCC (-.395) and MDSCC (0.372).Conclusions: Increase levels of copper in leukoplakia would be because of the fact that copper helpsin activating many angiogenic factors which further helps in tumor progression from premalignant tomalignancy.